2019
DOI: 10.21608/jes.2019.160156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compost Fertilization on Some Growth Parameters and Yield of Calendula Officinalis Variety (Costa Yellow)

Abstract: Calendula officinalis is classified as one of the most important medicinal crops that deserve improvement in production and quality. This research study was conducted to investigate the effect of using compost, as an organic amendment, to replace some of the mineral fertilizers normally used. The experiments were conducted in the open field in two successive seasons 2016-2017 and 2017-2018 at Applied Research Center for Medicinal Plants, National Organization for Drug Control and Research, (NODCAR) at Kafer El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Data in table (9) revealed that the highest value of carotenoids in flowers are by treatment (P25% + K 100% + with bio) are (11.0.and 11.4) (5.88 and 5.16) for 1st and 2nd season respectively compared to control without bio (6-8 and 6.4) in both seasons respectively. These results are in agreement with those reported by Abd El-Fatah et al (2019) and Abou-Sreea et al (2017).…”
Section: -Total Carotenoidssupporting
confidence: 94%
See 1 more Smart Citation
“…Data in table (9) revealed that the highest value of carotenoids in flowers are by treatment (P25% + K 100% + with bio) are (11.0.and 11.4) (5.88 and 5.16) for 1st and 2nd season respectively compared to control without bio (6-8 and 6.4) in both seasons respectively. These results are in agreement with those reported by Abd El-Fatah et al (2019) and Abou-Sreea et al (2017).…”
Section: -Total Carotenoidssupporting
confidence: 94%
“…Results in table (9) indicated that the highest values (29.3 and 28.5) of total carbohydrates were obtained by the treatment of P25% + K100% with bio for both seasons respectively. Meanwhile, the lowest total carbohydrates were showed in the control plants without bio (16.7and 17.0) in 1st and 2nd season respectively, while those data are in consent with these reported by Abd El-Fatah et al (2019), andHashem (2016).…”
Section: -Total Carbohydrates In Plant (Mg/g)supporting
confidence: 90%
“…In a study by Massoud et al [ 29 ], the authors found that in sandy soils, and in combination with the application of organic fertilizers, the water use efficiency of the crop was optimized at approximately 270 mm/season. The use of organic fertilization in calendula has reported promising results, and according to El-Fatah et al [ 30 ], organic fertilizers can replace 50% of synthetic fertilizers without compromising the performance of the crop. Overall, fertilization, and particularly nitrogen (N) fertilization, is believed to improve the yields and the agronomic characteristics of calendula [ 31 ].…”
Section: Tobacco Alternative Cropsmentioning
confidence: 99%